2019
DOI: 10.2139/ssrn.3482083
|View full text |Cite
|
Sign up to set email alerts
|

Financial Literacy and Attitudes to Cryptocurrencies

Abstract: We examine the relationship between financial literacy and attitudes to cryptocurrencies, using microdata from 15 countries. Our financial literacy proxy exerts a large negative effect on the probability of currently owning cryptocurrencies. The financially literate are also more likely to be aware of cryptocurrencies, and more likely to report that they do not intend to own them. We confirm the external validity of our financial literacy proxy and findings using data from a second novel survey of retail inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 79 publications
(76 reference statements)
1
13
0
4
Order By: Relevance
“…This could also mean that Vietnamese with higher financial literacy do not see fintech as an important tool for their financial transactions, as they may have strong access already to traditional financial facilities. This concurs with the findings of a recent study by Panos et al (2020), who also found financial literacy negatively relates to people's adoption of financial technology-based products in a study geared towards cryptocurrencies.…”
Section: Resultssupporting
confidence: 91%
“…This could also mean that Vietnamese with higher financial literacy do not see fintech as an important tool for their financial transactions, as they may have strong access already to traditional financial facilities. This concurs with the findings of a recent study by Panos et al (2020), who also found financial literacy negatively relates to people's adoption of financial technology-based products in a study geared towards cryptocurrencies.…”
Section: Resultssupporting
confidence: 91%
“…This suggests that mobile apps and platforms should be complemented by training. In a recent cross-country study, Panos and Karkkainen (2019) find that financial literacy is negatively related to cryptocurrency ownership. This suggests that less financially literate consumers have a limited understanding of the greater risk and reward trade-offs of cryptocurrencies relative to alternative asset classes.…”
mentioning
confidence: 95%
“…Studies with a similar search structure and conclusions about the "portrait" of a retail investor in cryptocurrencies came in the Netherlands (AFM, 2018) and Austria (Ritzberger-Grünwald Stix, 2018). Analysis of the level of financial literacy in cryptocurrency ownership has shown that investors who are more aware of them are less likely to trade with them (Panos & Karkkainen, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%